HUBUNGAN PENGETAHUAN KESELAMATAN DAN KESEHATAN KERJA (K3) DAN KETERSEDIAAN SARANA DAN PRASARANA TERHADAP PERILAKU PENGELOLAAN LIMBAH B3 DI PT X - Kafit, M.; Utami, Leni; Razali, Roni; Amaliah, Rizqi Ulla; Aini, Nur (Jurnal Liga Ilmu Serantau, 2026)
The behavior of hazardous waste (B3) management is influenced by knowledge of occupational health and safety (K3) and infrastructure. Inadequate K3 knowledge and insufficient infrastructure can affect the behavior of hazardous waste management. This study aims to determine the relationship between K3 knowledge and infrastructure on hazardous waste management behavior at PT X Pekanbaru City. This research employs a quantitative descriptive approach with a cross-sectional design. The sampling technique used was total sampling, resulting in a sample size of 50 participants. Data collection methods included primary data through K3 knowledge questionnaires, infrastructure questionnaires, and hazardous waste management behavior questionnaires. Secondary data were obtained from the administrative records of PT X. The research results indicate that there is a relationship between OHS (Occupational Health and Safety) knowledge (p = 0.002) and infrastructure facilities (p = 0.011) and hazardous waste (B3) management behavior (p < 0.05). The conclusion of this study shows that the majority of respondents have fairly good OHS knowledge, adequate infrastructure, and good behavior in managing hazardous waste (B3). It is recommended that the company consider improvements for further development, particularly in enhancing OHS knowledge, given that 66% of respondents have only a moderate level of OHS knowledge; therefore, it is important to strengthen education and training efforts regarding occupational health and safety (OHS)